EVALUASI PEMBANGUNAN PERTANIAN DI BALI SELAMA PJP I DAN PROGRAM PEMBANGUNAN PERTANIAN TAHUN 2000-2004 - KOMANG SUARTA; I.G.K. SWASTIKA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2000)
During the first stage long-term development (PJP I), almost all of agricultureproducts increased. However, start the sixth five years development (Pelita VI),production of agriculture diminishing return or levelling off, even decrease likeproduction of rice. Beside that, the agriculture of development to face the manyproblems linkage with agriculture land, irrigation water, pest and plant disease,production factors, post harvest, agriculture institution, etc.Implemented the regional autonomy in 2001, so needed changing theagriculture development paradigm, which involve planning aspect, businessorientation, behavior orientation, approach, and farmer’s participation.Program of agriculture development forward five years (2000-2004) namely:(1) Program of national food security, and (2) program of agribusiness development.Both of this programs its essence are to increase the welfare of agriculturecommunity and to direct the vision of 21-decade agriculture i.e.: modern, strong,and efficient.